Pitching injury prevention to baseballers and softballers: A review of the literature - Finch, C.; Valuri, G.; McGrath, A. (Monash University Accident Research Centre, 1996)
Baseball and softball are popular non-contact, non-collision team sports in Australia. Although softball originated as an indoor version of baseball, the two games have evolved into separate sports with different sets of rules and playing conditions. Both sports involve four main activities or skills: throwing, including pitching and fielding; catching; batting; and base running. The major difference in how the games are played is the technique by which the ball is pitched to the batter. In baseball, the ball is pitched in an overarm or sidearm action, whereas in softball an underarm action is used. Over the past twelve years there have been few studies published describing the epidemiology of baseball/softball injuries, particularly outside the US. Baseball and softball are associated with the largest number of injuries leading to an emergency room visit than any other sport in the United States. In Australia, baseball/softball is ranked as the 13th most common sport and recreational activity leading to an emergency department injury presentation for children and the 16th amongst adults. There are four main mechanisms of injury in softball/baseball: sliding (into a base); jamming or collisions (including hits by a ball or bat and collisions with other players); fails; and overuse. The overall aim of this report is to critically review both the formal literature and informal sources that describe injury prevention measures for baseball and softball. Most of the identified literature is from US studies, given the popularity of the sport in that country. However, a brief overview of the epidemiology of baseball and softball injuries, particularly from an Australian perspective, is given to set the scene for the subsequent discussion of countermeasures. Countermeasures for preventing baseball/softball injuries include the use of break-away/quick release bases; protective equipment such as helmets and chest protectors, ball design; safe playing environments eg padded walls and back stops; stretching, conditioning and technique programs before commencing play; adequate rehabilitation; and prompt treatment of injuries. Recommendations for further countermeasure research, development and implementation include additional research into the biomechanics of playing techniques and the mechanisms of injury; epidemiological studies to identify risk factors; further controlled evaluations of the effectiveness of countermeasures, use of break-away bases; further development of protective equipment; improvements to ball design; and improved player education.